2016
DOI: 10.1136/bmjopen-2016-012511
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of general practitioner's cancer-related gut feelings—a prospective cohort study

Abstract: BackgroundGeneral practitioners (GPs) use gut feelings to diagnose cancer in an early stage, but little is known about its impact.MethodProspective cohort study of patients in 44 general practices throughout the Netherlands, from January 2010 until December 2013. GPs completed a questionnaire regarding gut feelings, patient and GP characteristics, if they noticed a cancer-related gut feeling during patient consultation. Follow-up questionnaires were sent 3 months later requesting information about the patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 17 publications
(31 reference statements)
0
82
1
Order By: Relevance
“…Studies have shown that family physicians' gut feeling, or intuition, can be highly predictive of cancer in patients with nonspecific symptoms as well as palpable tumors and abdominal symptoms and that the ability improves with the physician's age and experience. [21,26,27]. Consultancy frequency represents another criterion of interest for further study; an increased frequency of consultancies has been documented during the year prior to a diagnosis of cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that family physicians' gut feeling, or intuition, can be highly predictive of cancer in patients with nonspecific symptoms as well as palpable tumors and abdominal symptoms and that the ability improves with the physician's age and experience. [21,26,27]. Consultancy frequency represents another criterion of interest for further study; an increased frequency of consultancies has been documented during the year prior to a diagnosis of cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Two other studies have reported positive predictive values (PPVs) of GPs gut feelings on 3%–35% concerning diagnoses of cancer. 2 3 These PPVs are comparable or substantial higher than the PPVs of most cancer alarm symptoms presented in primary care, which are mostly below 3%. 4 …”
Section: Introductionmentioning
confidence: 90%
“…In addition, patients may be referred based on their GP’s clinical suspicion of cancer or serious disease (their ‘gut feeling’). 25 26 GPs are also requested to indicate their suspicion of malignancy at this stage. The essential referral criteria are: There is no other urgent referral pathway suitable for this clinical scenario.…”
Section: Aimmentioning
confidence: 99%